2005
DOI: 10.1021/ja056490i
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of GDP-Mannose-3‘,5‘-Epimerase:  An Enzyme which Performs Three Chemical Reactions at the Same Active Site

Abstract: GDP-mannose-3′,5′-epimerase (GME) from Arabidopsis thaliana catalyses the epimerization of both the 3′ and 5′ positions of GDP-α-D-mannose to yield GDP-β-L-galactose. Production of the C5′ epimer of GDP-α-D-mannose, GDP-β-L-gulose, has also been reported. The reaction occurs as part of vitamin C biosynthesis in plants. We have determined structures of complexes of GME with GDP-α-D-mannose, GDP-β-L-galactose and a mixture of GDP-β-L-gulose with GDP-β-L-4-keto-gulose, to resolutions varying from 2.0 Å to 1.4 Å. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(143 citation statements)
references
References 76 publications
6
118
0
19
Order By: Relevance
“…1B and Table 2). As almost always observed in dinucleotide-binding proteins, a conserved water molecule bridges the interactions between the glycine-rich sequence and the diphosphate group (41,42). This water molecule is numbered water molecule 1 in 5␤-POR in complex with NADP ϩ because it displays the highest electron density of all water molecules.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…1B and Table 2). As almost always observed in dinucleotide-binding proteins, a conserved water molecule bridges the interactions between the glycine-rich sequence and the diphosphate group (41,42). This water molecule is numbered water molecule 1 in 5␤-POR in complex with NADP ϩ because it displays the highest electron density of all water molecules.…”
Section: Resultsmentioning
confidence: 89%
“…This proposal is corroborated by the observation that in sugar epimerases where the reaction is considered to proceed via a 1-2 hydrogen subtraction reaction by means of a temporary oxidation of a hydroxyl group to a keto-intermediate, the standard SDR orientation of the residues lysine and tyrosine is adopted, although all other substrate protein interactions differ considerably (42). On the other hand in enoyl-reductases (48), which catalyze a 1-4 hydrogen addition reaction similarly to 5␤-POR, the active site tyrosine side chain is also repositioned with respect to the lysine residue and the nicotinamide ring in the active site because the conserved YXXXK motif is replaced by a YXXMXXXK motif.…”
Section: ) (44)mentioning
confidence: 82%
“…GDP-α-L-Gal (GDP-Gal) was enzymatically synthesized according to previously outlined methods (39) and HPLCpurified using a linear ammonium formate gradient (40). UDP-β-L-Rha was enzymatically synthesized by a two-step reaction using UDP-α-D-Glc (UDP-Glc) as a substrate.…”
Section: Methodsmentioning
confidence: 99%
“…GDP-mannose-3′,5′-epimerase (ManEp) catalyzes the reversible conversion of GDP-D-mannose to GDP-Lgalactose and to GDP-L-gulose and it was suggested that this reaction is a key regulatory step of ascorbic acid (AsA) biosynthesis (Wolucka et al 2001;Major et al 2005). It has been recently indicated that in a comparison among kiwifruit genotypes that differ for the levels of AsA, the concentration of the vitamin is correlated to the high amount of GDP-mannose-3′,5′-epimerase and GDP-Lgalactose guanyltransferase also because, overexpressing the genes of the two enzymes in transgenic kiwifruit plants, a significant increase in AsA levels occurred (Bulley et al 2009).…”
Section: General Metabolismmentioning
confidence: 99%